Need of Nutraceuticals / Functional Food Products for Health Benefits to World-Wide People - Rajesh, K. Srivastava (Journal of Biotechnology and Biomedical Science, 2018)
Improved economic and developed people with their lifestyle have created many challenges of health issues (obesity, osteoporosis, cancer, diabetes, allergies and dental problems), due to selection of different food habits (such as consumption of manifold junk foods). It has created number of health problem (development of many diseases) related to nutritional deficiencies food. Nowadays, people have developed the habit for shifting of synthetic food ingredients to organic foods and ingredients, obtained from natural sources. In this regards, nutraceuticals food or its food products can perform important role in controlling the diseases via fulfilling all the health benefits to many people at worldwide. Incredible dietary supplements as nutraceuticals food (involvement in nutritional, immunologic and physiological functions) can help in prevention or treatment of many diseases (mitigating of gastrointestinal (GI) tract problem), as it is synthesized from raw herbals and lots of rapidly growing industries are reported to synthesize these natural products. And around 100 million people are found to take these products (power of plant based materials) for getting health benefits. It can work as drugs as health benefit of nutraceuticals via regulation/ control for diseases. Global nutraceuticals market had been valued for US$ 165.62 billion in 2014 and it would be grow the value of US$ 278.96 billion by 2021 with compound annual growth rate of 7.3%. This proposed paper will discuss the different types of nutraceuticals food or its functional components involved in prevention or treatment of diseases.
Keywords: Lifestyle; Health issues; Nutritional deficiencies; Diseases; Nutraceuticals foods; Treatment; Prevention.